Pengaruh Inovasi Produk Dan Brand Image Terhadap Keputusan Pembelian Produk Kosmetik Lipstik Hanasui (Studi Kasus Pada Mahasiswa Stie Wikara) - Utami, Indri Putri; Suhendi, Dede; Sulistyanto, Tri Hadi; Darmawan, Meimey; Rustina Dewi Werdiasih (Awatara Publisher, 2025)
This research is motivated by the rapid growth of the cosmetic industry in Indonesia, particularly in lipstick products which are an essential need for women. Although Hanasui is known for its affordable prices and unique product innovations such as the Mattedorable Lip Cream Matcha Latte Edition, in 2024 Hanasui did not release any new innovations, while its competitors continued to innovate. This gap indicates the need for an in-depth analysis of product innovation and brand image on purchase decisions. The main objective of this study is to analyze the influence of product innovation and brand image on the purchase decision of Hanasui lipstick among undergraduate students at STIE Wikara. This research used a quantitative approach with descriptive and causal designs, data collection through questionnaires distributed to undergraduate students at STIE Wikara, and data analysis using SmartPLS to test the measurement and structural models. The results showed that product innovation had a positive and significant effect on purchase decisions, while brand image did not have a significant partial effect. However, simultaneously, product innovation and brand image had a significant effect on purchase decisions. In conclusion, product innovations relevant to consumer trends and needs can increase the purchase decisions of Hanasui lipstick, while brand image needs to be strengthened to support the implemented innovations. This research contributes to the development of marketing management knowledge and provides practical applications for companies to enhance competitiveness through product innovation and brand image strengthening.